Women-Quota Policy in Australian Labor Party - Maylita Kusuma Putri (Magister Ilmu Politik Universitas Hasanuddin, 2015)
Abstract : Women equality recently becomes an issue globally. It becomes debatable since the issue has pro and con, both from men and women. After the women vote was implemented in Australia, government needed to balance the implementation both in public and political life. It was because when government pleased the women to stand up in the parliament, means that women have the same value like men. In 1990s, women as parliament representative became a focus issue on international and national attention. Many arguments rise said that women’s interests should be represented well. They suggested that women needed to make differentiate in politics and made change in the representative. But, even the presence of women in legislature, it was still far from women-friendly. It brought the Australian Labor Party to implement the women-quota policy.Keywords: Women-Quota Policy, Australian Labor Party, Gender Equality